2014
DOI: 10.1111/1541-4337.12087
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Mixed‐Species Biofilms in the Context of Food Safety

Abstract: Formation of mixed-species biofilms constitutes a common adaptation of foodborne pathogens and indigenous microbiota for prolonged survival in their food niche. Nevertheless, the potential role of mixed-species biofilms in food safety remains to be elucidated. The formation of mixed-species biofilms on food and food processing surfaces depends on various physical, chemical, and biological processes including species composition, especially of the indigenous microbiota and nutrients, food types, temperature, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 214 publications
(378 reference statements)
2
37
0
2
Order By: Relevance
“…In vitro, biofilm formation between LAB and yeast species isolated from many foods has been reported (20,(27)(28)(29). In the natural environment of Spanish-style green olive fermentation, mixed-species biofilms between yeasts and lactobacilli in the skins of fruits have also been found (11,12,14,15,19).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, biofilm formation between LAB and yeast species isolated from many foods has been reported (20,(27)(28)(29). In the natural environment of Spanish-style green olive fermentation, mixed-species biofilms between yeasts and lactobacilli in the skins of fruits have also been found (11,12,14,15,19).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, some studies have also reported biofilm formation by some of the Pseudomonas and Aeromonas bacterial strains isolated from different types of foods (i.e., raw milk, fish and meat etc. ; Jahid and Ha 2014; Yuan et al . 2018; Liu et al .…”
Section: Resultsmentioning
confidence: 99%
“…In food industry environment, the non-detection of negative catalase microorganisms would not be a problem because biofilms are formed by mixed species (Colagiorgi et al, 2017;Elias & Banin, 2012;Phillips, 2016) and therefore the use of the biodetector would show microbial activity. Biofilms formed by mixed species constitutes a general adaptation of foodborne pathogens and microbiota associated to the food-processing environment for extended survival in their food niche (Jahid & Ha, 2014).…”
Section: Detection Of Biofilms Using Dem and The Different Biodetectomentioning
confidence: 99%
“…However, biofilms are formed by multiple microbial species in natural environments (Manuzon & Wang, 2007;Montañez-Izquierdo, Salas-Vázquez, & Rodríguez-Jerez, 2012;Moons, Michiels, & Aertsen, 2009;Percival, Walker, & Hunter, 2000). Different studies have outlined the significance of biofilms formed by mixed species for the food industry (Jahid & Ha, 2014;Percival et al, 2000). The importance for this industry is attributed to the existence of interspecies interactions that might enhance not only the survival of pathogens to sanitizers, disinfectants, UV light, or desiccation, but also its persistence on food-contact surfaces (Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%